The Impact of a Professional Development Program on Science Teachers' Classroom Performance: Teaching Nature of Science - İREZ, OSMAN SERHAT (DERGIPARK AKAD, 2019)
The studies about classroom practices in Nature of Science (NOS)-Professional Development (PD) contexts are considered scarce to detect the problems caused by curriculum, textbook, teacher, classroom environment, cultural differences and therefore more studies in different cultural contexts are needed in this field. Thus, the effectiveness of professional development program on teachers' classroom practices was investigated through video records and teachers' reports on understanding how NOS affects their classroom practices. The results show that the relationship between teachers' views about nature of science and their practices is complex and not to impressionable, factors as gender, experience about NOS or History of science (HOS) courses, academic degree, professional experience, and the activity numbers. Moreover, explicit NOS instruction is relatively more effective in increasing classroom practices and also NOS views.
Keywords: professional development program; nature of science; pedagogical content knowledge; classroom practices; science teacher; STUDENTS; INSTRUCTION; CONCEPTIONS; KNOWLEDGE; INQUIRY; VIEWS